Distribution of eight serotypes of Ureaplasma urealyticum in cases of non-gonococcal urethritis and of gonorrhoea, and in healthy persons. Issue 4 (August 1976) - Piot, P
Abstract : The isolation rate of Ureaplasma urealyticum was 57 per cent. from 47 patients with non-gonococcal urethritis, 40 per cent. from forty patients with gonorrhoea, 47 per cent from healthy sailors, and 53 per cent. from healthy students and laboratory technicians. No difference in distribution of eight serotypes among 45 isolates from these groups was demonstrated and no particular serotype could be correlated with disease symptoms.